The association of multiple metrics for evaluating antimicrobial use in U.S. beef feedyards - Apley, Michael D.; Schrag, Nora F. D.; Amrine, David E.; Lubbers, Brian V.; Singer, Randall S. (Frontiers in Veterinary Science, 2023)
In order to accurately portray antimicrobial use in food animals, the need for standardized metrics, and an understanding of the characteristics of different metrics, has long been recognized. Fourteen U.S. feedyards were used to evaluate the effects of using centralized constants such as defined daily dose (DDD) and defined course dose (DCD) applied to the weight of medically important antimicrobials by class (mg) as opposed to using electronic individual animal treatment records and lot level in-feed antimicrobial records obtained from the same population. Three numerators were calculated directly from recorded data for each drug product: the number of antimicrobial regimens associated with indication (Reg), milligrams of drug administered per regimen (mg), and calendar days of administration for each regimen (CDoA). There were four use indications to which numerators were assigned: liver abscess control (LAC), bovine respiratory disease (BRD), lameness (lame), or all other indications combined (other). Three denominators were also calculated directly from the data, these being the number of days animals were present (head days), number of cattle received (head in), and kilograms of live weight sold (kg-LW). Numerators and denominators were calculated at the lot level. The use of DDD or DCD was explored to determine how their use would affect interpretation of comparisons between lots or feedyards. At the lot level across both study years, the lot estimate of nDDD differed from the CDoA value by >25% in 56.1% of the lots. The number of Defined Course Doses (nDCD) was then compared to the number of Regimens (Reg). Comparing nDCD to Reg at the lot level across both study years, the lot estimate of nDCD differed from the Reg value by >25% in 51.3% of lots Both year and metric were also shown to affect numerical feedyard ranking by antimicrobial use according to seven different metrics. The analysis reported here adds to the body of literature reporting substantial effects of metric choice on the conclusions drawn from comparing antimicrobial use across multiple production sites.